2010
DOI: 10.1200/jco.2009.26.3947
|View full text |Cite
|
Sign up to set email alerts
|

Rearrangement ofMYCIs Associated With Poor Prognosis in Patients With Diffuse Large B-Cell Lymphoma Treated in the Era of Rituximab

Abstract: The presence of a MYC rearrangement is a strongly adverse prognostic factor in CHOP-R-treated patients and can be used in combination with patients' age and IPI to accurately predict clinical outcome. In DLBCL, rearrangement of MYC is rarely found as the sole genetic abnormality and the poor prognosis of these patients is likely to reflect a synergistic effect alongside deregulation of BCL6 or BCL2.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

26
422
8
12

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 521 publications
(468 citation statements)
references
References 38 publications
26
422
8
12
Order By: Relevance
“…The presence of MYC rearrangements in patients with diffuse large B-cell lymphoma treated with Rituximab, Cyclophosphamide, Doxorubicin, Vincristine and Prednisone (R-CHOP) has been shown to be associated with poor prognosis. 3,4 In particular, the so-called 'double-hit' lymphomas that are characterized by MYC rearrangement and a concurrent rearrangement of other B-cell lymphomaassociated genes such as BCL2 or BCL6 are associated with poor response to therapy, aggressive clinical course and dismal prognosis. [5][6][7] These lymphomas are classified as 'B-cell lymphoma, unclassifiable with features intermediate between diffuse large B-cell lymphoma and Burkitt lymphoma' in the current 2008 WHO classification of hematopoietic neoplasms.…”
mentioning
confidence: 99%
“…The presence of MYC rearrangements in patients with diffuse large B-cell lymphoma treated with Rituximab, Cyclophosphamide, Doxorubicin, Vincristine and Prednisone (R-CHOP) has been shown to be associated with poor prognosis. 3,4 In particular, the so-called 'double-hit' lymphomas that are characterized by MYC rearrangement and a concurrent rearrangement of other B-cell lymphomaassociated genes such as BCL2 or BCL6 are associated with poor response to therapy, aggressive clinical course and dismal prognosis. [5][6][7] These lymphomas are classified as 'B-cell lymphoma, unclassifiable with features intermediate between diffuse large B-cell lymphoma and Burkitt lymphoma' in the current 2008 WHO classification of hematopoietic neoplasms.…”
mentioning
confidence: 99%
“…13,16 In each case, mRNA sample from FFPE lymphoma tissue was available from the previous study. Local ethical guidelines were followed for the use of archival tissues for research with the approval of the ethics committees of the involved institutions.…”
Section: Materials and Methods Patient Materials And Data Setsmentioning
confidence: 99%
“…13,16 Primer Design and Validation PCR primer pairs were designed for the 20 classifier genes that are commonly present in different microarray platforms, 5 NF-kB target genes that are characteristically enriched in their expression in ABC-DLBCL, 4,5 and 3 reference genes (Supplementary Table S1). The reference genes were selected as they are stably expressed in lymphoid tissues, but not affected by genomic copy number changes in lymphoma, nor involved in lymphomagenesis.…”
Section: Materials and Methods Patient Materials And Data Setsmentioning
confidence: 99%
See 1 more Smart Citation
“…9,10 Several studies have reported that MYC translocations independently predicted significantly poor survival in DLBCL patients. [11][12][13][14][15][16] However, other studies found inconsistent results [17][18][19] or limitations of its prognostic significance. 20,21 The clinical significance of Myc overexpression in DLBCL has also been the source of much attention and controversy.…”
mentioning
confidence: 99%